Improving Cell-to-Cell and Cell-to-Matrix Contact inside Microphysiological Systems - Olaizola Rodrigo, Claudia; Castro-Abril, Héctor; Perisé-Badía, Ismael; Pancorbo, Lara; Ochoa, Ignacio; Monge, Rosa; Oliván, Sara (Jornada de Jóvenes Investigadores del I3A, 2024)
Innovative microfluidic technology aims to create more realistic in vitro simulations of human tissues. Organ-on-a-chip (OoC) devices within microfluidic chips mimic in vivo environments but face limitations due to inert material between compartments, hindering cell interaction. Current membranes made of PDMS or plastic impede proper cell-nutrient exchange and induce unexpected cell responses. This work focuses on minimizing inert materials while maximizing cell-matrix and cell-cell interactions in microfluidic chips.